Konsep Dasar Dan Paradigma Manajemen Pembelajaran Paud - Meril Qurniawan (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2017)
Learning can not be separated from the learning and teaching process, these two things can also be used as a scientific foundation in terms of basic concepts of learning. Scientific grounding in learning is related to philosophical, psychological, sociological, and communication ground. Philosophically learning means returning to human beings about the meaning of life that can be passed through the process of imitating, understanding, emerging, studying, and doing. While in the science of psychology, learning will be able to change human behavior while making human conscious must be like what. Some schools of psychology are still the foundation of education, including cognitive and behavioristic flows. Sociologically, with human learning can socialize and build society according to goals and expectations. In the end man will be aware of his position as a social being who can not live alone. Similarly, the foundation of communication that will not be removed from the learning process because the essence of learning is communication so that someone is able to understand. The direct involvement of learners in the educational process becomes a directed experience that is expected to be rooted in the students themselves. Because experience provides a positive direction on selection and organization of appropriate educational materials and methods, this is an effort to provide new directions for school work. Thus learn a process that can not directly spontaneous all innate potential, slowly to the ongoing process, by presenting various problems and conflicts that can be resolved or resolved by the child actively